2019
DOI: 10.1128/iai.00072-19
|View full text |Cite
|
Sign up to set email alerts
|

New Perspectives on Galleria mellonella Larvae as a Host Model Using Riemerella anatipestifer as a Proof of Concept

Abstract: Galleria mellonella larvae have been used as a host model to study interactions between pathogens and hosts for several years. However, whether the model is useful to interrogate Riemerella anatipestifer infection biology remained unknown. This study aimed to exploit the potential of G. mellonella larvae and reveal their limitations as a host model for R. anatipestifer infection. G. mellonella larvae were shown to be effective for virulence evaluations of different R. anatipestifer strains. Furthermore, the vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 58 publications
(81 reference statements)
1
12
0
Order By: Relevance
“…Induction of expression was highest at 4 h pi, and thereafter decreased over the time course despite the presence of a persistent infection. Similar observations were made in an RT-qPCR study of G. mellonella innate immune responses to infection with Riemerella anatipestifer , a Gram-negative bacterium, where genes involved in innate immunity (e.g., encoding AMPs and opsonin), were highest at 4 h pi, and declined over time ( Liu et al., 2019 ). In this study, the trend between the presence of protein and the corresponding mRNA improved over the course of infection, but the abundance of protein was largely inconsistent with gene expression signals, with only 20% in agreement between 48-168 h pi.…”
Section: Discussionsupporting
confidence: 73%
“…Induction of expression was highest at 4 h pi, and thereafter decreased over the time course despite the presence of a persistent infection. Similar observations were made in an RT-qPCR study of G. mellonella innate immune responses to infection with Riemerella anatipestifer , a Gram-negative bacterium, where genes involved in innate immunity (e.g., encoding AMPs and opsonin), were highest at 4 h pi, and declined over time ( Liu et al., 2019 ). In this study, the trend between the presence of protein and the corresponding mRNA improved over the course of infection, but the abundance of protein was largely inconsistent with gene expression signals, with only 20% in agreement between 48-168 h pi.…”
Section: Discussionsupporting
confidence: 73%
“…The above results showed that the absence of fur led to a potentially increase in intracellular iron content, indicating that Fur is involved in the regulation of iron transport. Therefore, to verify whether R. anatipestifer CH-1 Fur can regulate the transcription of putative iron uptake-related genes, we detected the mRNA levels of TonB-dependent receptor genes B739_0103 and B739_0173 , which were up-regulated in an iron-limited environment and considered iron uptake-related genes [ 31 , 33 ]. The results showed that the transcription of B739_0103 and B739_0173 was markedly increased in R. anatipestifer CH-1 ∆fur compared to that in the wild-type strain, and their transcript levels were not affected when 100 µM EDDHA was added to the GCB medium (Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, we demonstrated that a fur deletion strain of R. anatipestifer showed reduced virulence in the Galleria mellonella model [ 33 ]. To investigate if Fur plays a role in the pathogenesis of R. anatipestifer CH-1 in poultry, we used a duckling model [ 29 , 30 ] to determine the LD 50 of the fur mutant.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations